How Fitrah Based Education predict parent-child relationships in early childhood? - Salma, Hasna Hafizhah; Veni, Karlina Listra (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2024)
Homeschooling in early childhood is not just learning like in formal school, but also doing many different activities to stimulate children's development. When homeschooling starts, parents are required to be involved and maintain a relationship with their children. One approach that can be used in carrying out learning activities from home is Fitrah-Based Education (FBE). This study aims to look at the role of FBE in the relationship between parents and children. This study uses a mixed method with a cross-sectional design. Data was collected using a reflection of Child-Parent Relationships Scale (CPRS) filled out by parents and observations via social media Instagram and Qur’an Based Play’s community WhatsApp groups. Quantitative data analysis uses correlation and linear regression techniques, qualitative data analysis uses observation recording techniques. The results show that the routine of various Fitrah-based education activities can predict parent-child relationships (p-value 0.05) by 9.3% on the conflict dimension and 8% on the closeness dimension. This research can be useful for parents at home and the community of Fitrah-based education activists in general. The limitation is a threat to external validity.